Psychological consequences of road traffic accidents for children and their mothers. - Bryant, B; Mayou, R; Wiggs, L; Ehlers, A; Stores, G (2004)
BACKGROUND: Little is known about the psychological and behavioural consequences of road traffic accidents for children. The study aimed to determine the outcome of road traffic accidents on children and their mothers. METHOD: A 1-year cohort study of consecutive child attenders aged 5-16 years at an Accident and Emergency Department. Data were extracted from medical notes and from interview and self-report at baseline, 3 months and 6 months. RESULTS: The children had an excellent physical outcome. Fifteen per cent suffered acute stress disorder; 25% suffered post-traumatic stress disorder at 3 months and 18% at 6 months. Travel anxiety was frequent. Post-traumatic consequences for mothers were common. CONCLUSION: Psychological outcome was poor for a minority of children and associated with disability, especially for travel. There were significant family consequences. There is a need for changes in clinical care to prevent, identify and treat distressing and disabling problems.